Development and validation of main spectral profile for rapid identification of Yersinia ruckeri isolated from Atlantic salmon using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry - Ojasanya, Rasaq A.; Gardner, Ian A.; Groman, David; Saksida, Sonja; Saab, Matthew E.; Thakur, Krishna K. (Frontiers in Veterinary Science, 2022)
Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) allows rapid and reliable identification of microorganisms. The accuracy of bacterial identification using MALDI-TOF MS depends on main spectral profiles (MSPs) provided in a quality-assured commercial reference library, which requires ongoing improvement. This study aimed to develop and validate an in-house MALDI-TOF MS MSP to rapidly identify Yersinia ruckeri isolated from Atlantic salmon (Salmo salar). The novel MSP was prepared using an isolate of Y. ruckeri recovered from Atlantic salmon and confirmed by 16S rRNA gene sequencing. Subsequently, a validation set which comprises 29 isolates of Y. ruckeri were examined from three fishes: Atlantic salmon (Salmo salar) (n = 26), American eel (Anguilla rostrata) (n = 1), and Atlantic cod (Gadus morhua) (n = 2). These isolates were randomly selected from the Atlantic Veterinary College, Aquatic Diagnostic Services Bacteriology Laboratory's culture collection to validate the novel MSP. Analytical sensitivity of MALDI-TOF MS using the novel MSP to identify the validation set was 86.2%. Repeatability was assessed by acquiring spectra from 30 different spots of a randomly-selected isolate of Y. ruckeri, and analyzed spectra from each spot were compared against the novel MSP. The coefficient of variation was 3.3%. The novel MSP clustered with Bruker MSPs (n = 3) of Y. ruckeri in the reference library and did not falsely identify any closely related bacteria to Y. ruckeri. This study reports the development of a novel MSP of high analytical sensitivity and specificity for rapid identification of Y. ruckeri using MALDI-TOF MS.